2021
DOI: 10.1002/acm2.13383
|View full text |Cite
|
Sign up to set email alerts
|

Compressed‐sensing accelerated magnetic resonance imaging of inner ear

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This combination of the SENSE technique and iterating L1-regularized de-noising filters has been applied to various sequences, and several groups have reported that it achieves improved image quality and shortened acquisition time. [9][10][11] In contrast, it has been reported that iterating L1-regularized de-noising filters can be applied to EPI (EPI with L1-regularized iterative SENSE-based DWI [L1-DWI]) to improve the image quality of EPI-based DWI. [12][13][14][15][16] Although there are several problematic issues behind iterative approaches, including the long computation time, variation of the performance due to the details of fine-tuning, and the influence of the spatial signal distribution in target images, the latest hardware advancements have markedly reduced the computation time and implemented well-optimized fine-tuning.…”
Section: Introductionmentioning
confidence: 99%
“…This combination of the SENSE technique and iterating L1-regularized de-noising filters has been applied to various sequences, and several groups have reported that it achieves improved image quality and shortened acquisition time. [9][10][11] In contrast, it has been reported that iterating L1-regularized de-noising filters can be applied to EPI (EPI with L1-regularized iterative SENSE-based DWI [L1-DWI]) to improve the image quality of EPI-based DWI. [12][13][14][15][16] Although there are several problematic issues behind iterative approaches, including the long computation time, variation of the performance due to the details of fine-tuning, and the influence of the spatial signal distribution in target images, the latest hardware advancements have markedly reduced the computation time and implemented well-optimized fine-tuning.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Compared with the traditional full sampling and recompressing process, it can carry out a low-power and high-efficiency data process. Accordingly, various CS algorithms have been proposed, [5][6][7] and well applied in many fields, for instance, wireless sensor networks and loT, [8][9][10] electrocardiogram data compression, [11][12][13] and magnetic resonance imaging, [14][15][16] to name a few. In recent years, there has been an increasing interest in the hardware implementation of CS, [17][18][19][20] which originally suffered from several limitations, including limited scalability and separate sensing and sub-sampling.…”
mentioning
confidence: 99%